2023
DOI: 10.1186/s40364-023-00469-6
|View full text |Cite
|
Sign up to set email alerts
|

Liquid biopsy by analysis of circulating myeloma cells and cell-free nucleic acids: a novel noninvasive approach of disease evaluation in multiple myeloma

Abstract: Multiple myeloma (MM) is an incurable hematological cancer with high spatial- and temporal-heterogeneity. Invasive single-point bone marrow sampling cannot capture the tumor heterogeneity and is difficult to repeat for serial assessments. Liquid biopsy is a technique for identifying and analyzing circulating MM cells and cell products produced by tumors and released into the circulation, allowing for the minimally invasive and comprehensive detection of disease burden and molecular alterations in MM and monito… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 114 publications
0
3
0
Order By: Relevance
“…Since then, it has been established that the concentration of cfDNA is elevated in cancer patients [35]. In addition, the use of different sequencing techniques, ranging from targeted identification of patient-specific rearrangements of immunoglobulin variable regions to genome-wide analysis with an untargeted approach, allows for the detection of cancer-derived, circulating tumor DNA (ctDNA) [36]. The concentration of ctDNA and the tumor fraction (percentage of ctDNA in cfDNA) correlate with the disease stage in plasma cell dyscrasias, being higher in multiple myeloma patients compared with individuals with smoldering myeloma and monoclonal gammopathy of undetermined significance [37].…”
Section: Circulating Tumor Dnamentioning
confidence: 99%
“…Since then, it has been established that the concentration of cfDNA is elevated in cancer patients [35]. In addition, the use of different sequencing techniques, ranging from targeted identification of patient-specific rearrangements of immunoglobulin variable regions to genome-wide analysis with an untargeted approach, allows for the detection of cancer-derived, circulating tumor DNA (ctDNA) [36]. The concentration of ctDNA and the tumor fraction (percentage of ctDNA in cfDNA) correlate with the disease stage in plasma cell dyscrasias, being higher in multiple myeloma patients compared with individuals with smoldering myeloma and monoclonal gammopathy of undetermined significance [37].…”
Section: Circulating Tumor Dnamentioning
confidence: 99%
“…Overall, liquid biopsies may provide a dynamic and comprehensive picture of the genomic landscape in MM and, even more, a non-invasive approach to monitor tumor burden. However, these methods are still novel and demand further research, especially when comparing results with matched BM assessments [137,138]. Therefore, the implementation of liquid biopsies for MM requires validation and harmonization of the assays [123].…”
Section: Overall Comparison Of Contemporary Mrd Strategiesmentioning
confidence: 99%
“…CTPCs are released from the primary tumor or metastatic sites into the bloodstream and are responsible for dissemination and extramedullary disease. CfDNA consists of degraded DNA fragments released into the circulation from tumor cells and is molecularly distinct in total extracellular DNA [98]. It has been demonstrated that CTPC can be detected in up to 80-90% of newly diagnosed patients and even in 100% of patients at MM relapse [99,100].…”
Section: Peripheral Blood Techniques For Mrd Assessmentmentioning
confidence: 99%